If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 = 3y + 6 Reorder the terms: 90 = 6 + 3y Solving 90 = 6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 90 + -3y = 6 + 3y + -3y Combine like terms: 3y + -3y = 0 90 + -3y = 6 + 0 90 + -3y = 6 Add '-90' to each side of the equation. 90 + -90 + -3y = 6 + -90 Combine like terms: 90 + -90 = 0 0 + -3y = 6 + -90 -3y = 6 + -90 Combine like terms: 6 + -90 = -84 -3y = -84 Divide each side by '-3'. y = 28 Simplifying y = 28
| 18y-20=1y+80 | | 3(3y-6)= | | 1p-1=5p+3p-8 | | 7x-6=6x-1 | | 1-p=5p+3p-8 | | 0.80X+.50(18-x)=.10(99) | | 9x=5y+13 | | 18=x+12 | | -3w-8+4w=-1+15 | | 4.5+x=4.5 | | 2(x-1)=x | | 0.20x+.50(2-x)=.10(-14) | | 0.36(12)+0.04x=0.12(18+x) | | -5(-2)(-6)= | | 2(4c-3)-7=6c+7 | | 7x+17=6x+9 | | 2r+2+4r=-16 | | 2b+7b=-18 | | 3+5m+8=16 | | 4x+39=-x+4 | | 4+6v+4=8 | | 6x+3=-51 | | -3n-4+4n=-5 | | -8x+7x=-6 | | 5(x)+12=27 | | -3x^2+6x-2=0 | | 8(2n-1)=(3n+1)+2 | | 61=t+27 | | 15x^2+4x=4 | | -2-3(y+6)+4y=36 | | 0.7x-5=0.6 | | 64=y-82 |